This text studies the shared meanings inside an emerging social mobilization for the defence of water at the Cuenca de México (CM). This work stems from a doctoral research on such a mobilization’s recent developments (2005-2009) and its potential social - Garavito González, Leonardo (Universidad del Rosario, 2012)
This text studies the shared meanings inside an emerging social mobilization for the defence of water at the Cuenca de México (CM). This work stems from a doctoral research on such a mobilization’s recent developments (2005-2009) and its potential social reflexive influence. The shared meanings  analysis applied here serves on one hand to identify and rank the mobilization’s main ideas and  proposals. On the other hand, this paper assesses the mobilization’s critical and constructive input to the present political and social order at the CM region. Indeed, the mobilization’s recent development  is indicating that water’s social action and organization are growing at the CM, and that social  conflict and unrest against the water’s ruling definitions and uses are increasing too. This text is divided in three sections: first, a case study presented with central theoretical and  methodological considerations; second, the mobilization´s shared meanings analysis and main results, and third, some conclusions about t  e mobilization’s main challenges and how its potential  social reflexive influence is developed.